Presenting Sustainable Design Principles of Contemporary Urban Public Realms in Historical Cities Through Comparative Analysis of Piazza Del Campo and City Center of Chandigarh - Sadeghi, Ali Reza; Ahmadi, Ferial (European Journal of Sustainable Development, 2018)
In the current research descriptive–analytic method has been applied to present design criteria of urban public realms with historical context. In order to achieve these criteria first, two examples of successful and unsuccessful urban public realms both have a historical background with the difference that one of them is a historical square and the other one is modern city center in historic city have been assessed. Then, with emphasis on extracted design principles and criteria of successful case study (Piazza del Campo) and specific historical and climate features of the bed, suggestion for revitalization lost historical, cultural and social values of unsuccessful case study (city center of Chandigarh) have been presented. These suggestions emphasize on designing pedestrian channels, unifying the entire complex by help of chattas at upper floors and by a continuous arcade at the lower floors and etc. It should be mentioned that research results indicate that in restoring historical public realms or designing modern public realms in historical cities, an attempt shall be made to create urban patterns adopting and adjusting the historical values with respect to future needs and knowledge of microclimate. Keywords: Public Realm, Historical Cities, Piazza Del Campo, City Center of Chandigarh